2007
DOI: 10.1103/physrevb.76.054104
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance investigation ofMn2+ions and their dynamics in Mn-dopedSrTiO3

Abstract: ron spin resonance, lattice position and dynamic properties of Mn 2+ ions were studied was tric ACS numbers: 61.72.-y, 76.30.Fe, 77.84.Dy Using elect in 0.5 and 2 % manganese doped SrTiO 3 ceramics prepared by conventional mixed oxide method. The measurements showed that Mn 2+ ions substitute preferably up to 97 % for Sr if the ceramics is prepared with a deficit of Sr ions. Motional narrowing of the Mn 2+ ESR spectrum observed when temperature increases from 120 K to 240-250 K that was explained as a manifest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 27 publications
5
50
0
Order By: Relevance
“…Specifically, characteristic values of hyperfine splittings and Lande g factors in the corresponding EPR spectra have been very effective in distinguishing between the SrMn, [13]. The EPR spectra of TiMn sample consist of a sextet of lines with a hyperfine splitting of 74 Oe and a Lande g factor of 1.997, and is characteristic of the expected presence of Mn 4+ ions doped at the Ti site [11,12].…”
Section: Mn Doping Inmentioning
confidence: 98%
See 1 more Smart Citation
“…Specifically, characteristic values of hyperfine splittings and Lande g factors in the corresponding EPR spectra have been very effective in distinguishing between the SrMn, [13]. The EPR spectra of TiMn sample consist of a sextet of lines with a hyperfine splitting of 74 Oe and a Lande g factor of 1.997, and is characteristic of the expected presence of Mn 4+ ions doped at the Ti site [11,12].…”
Section: Mn Doping Inmentioning
confidence: 98%
“…Electron paramagnetic resonance (EPR) has been widely employed to investigate the valences and local environments of the doped Mn ions in the STO lattice [11][12][13]. Specifically, characteristic values of hyperfine splittings and Lande g factors in the corresponding EPR spectra have been very effective in distinguishing between the SrMn, [13].…”
Section: Mn Doping Inmentioning
confidence: 99%
“…Ceramic samples of SMnT were prepared by a mixed oxide technology described elsewhere [27]. Preponderant incorporation of Mn 2+ into A sites of the perovskite structure was confirmed by energy dispersive X-ray spectra [27], electron diffraction and Raman spectroscopy [28], and by Mn 2+ ESR analysis [29]. Fig.…”
Section: Magnetoelectricity In a Multiglass Systemmentioning
confidence: 99%
“…Strontium titanate is a model material of the perovs kite family [1,2]. It has been found that SrTiO 3 : Mn undergoes dielectric relaxation [3][4][5][6][7], the nature of which still remains unclear [8][9][10]. Kleemann et al [11] established that, in ceramic samples of the stron tium manganese titanate Sr 0.98 Mn 0.02 TiO 3 , the polar glass and spin glass phases coexist and the magneto electric effect manifests itself.…”
Section: Introductionmentioning
confidence: 99%